2019
DOI: 10.1016/j.anbehav.2018.11.005
|View full text |Cite|
|
Sign up to set email alerts
|

A house of cards: bias in perception of body size mediates the relationship between voice pitch and perceptions of dominance

Abstract: Theories of the evolution of low voice pitch in men are based on the idea that voice pitch is an honest indicator of physical dominance, but relationships among pitch, physical body size and strength among same sex adults voice are weak and unstable. Nevertheless, judgements of body size based on voice pitch are the result of perceptual bias that low frequencies sound large. If dominance judgements are based in part on perception of size, then dominance perception could also be the result of perceptual bias. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 79 publications
(115 reference statements)
2
36
0
Order By: Relevance
“…More puzzling, however, is the abundance of evidence suggesting that listeners readily use f o as a cue for inferring a variety of traits even within sex, attributing greater size, strength, and formidability to adult male voices with lower f o 12 , 14 , 18 , 19 . Yet, scholars debate the accuracy of these perceptions 11 , 17 , 18 , 20 , 21 . According to one hypothesis, attention to men’s f o is the perceptual by-product of a broader tendency to associate low-frequency sounds with physically larger sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More puzzling, however, is the abundance of evidence suggesting that listeners readily use f o as a cue for inferring a variety of traits even within sex, attributing greater size, strength, and formidability to adult male voices with lower f o 12 , 14 , 18 , 19 . Yet, scholars debate the accuracy of these perceptions 11 , 17 , 18 , 20 , 21 . According to one hypothesis, attention to men’s f o is the perceptual by-product of a broader tendency to associate low-frequency sounds with physically larger sources.…”
Section: Introductionmentioning
confidence: 99%
“…According to one hypothesis, attention to men’s f o is the perceptual by-product of a broader tendency to associate low-frequency sounds with physically larger sources. Hence, listeners may perceive low frequencies to be intimidating even when f o is unrelated to the size of the sound producer 18 , 21 . However, lower f o has been found to predict men’s status, as well as mating and reproductive success 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Although only one paper 5 besides the current one has reported the specific interaction effect of testosterone and cortisol on male f o , the meta-analysis reported here suggests that the interaction is robust. There is widespread agreement 5,11,27,40,46 that low male f o evolved to exaggerate apparent size by leveraging a predisposition to perceive low frequencies as emanating from large sound sources. Phylogenetic reconstruction suggests that relatively male f o evolved in the common ancestor of the catarrhine primates after their divergence from platyrrhines approximately 43.5mya 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Costly signaling theory (originally proposed by 22,23 , but see 24 ) which concerns the transmission of reliable information between signalers and receivers, is a useful theoretical tool to answer this question and helps us understand the maintenance of signal honesty via receiver-independent (production costs, developmental costs, maintenance costs) and receiver-dependent costs (e.g., retaliation costs, vulnerability costs; see 25,26 for reviews). Recently, some authors 27,28 have pointed out weak receiver-independent costs associated with men's f o and concluded that men's f o does not signal formidability. Others [29][30][31] suggest that men's f o is likely to be partly honest.…”
mentioning
confidence: 99%
“…The sound pressure level of all voices will be amplitude normalized to 70 dB using the root mean squared method (following Armstrong et al, 2019). Voice recordings will then be presented via headphones and all raters will rate each voice individually on attractiveness using a 1 (very unattractive) to 7 (very attractive) scale.…”
Section: Attractiveness Ratingsmentioning
confidence: 99%